2017
DOI: 10.1080/13607863.2017.1402292
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal trajectories of subjective care stressors: the role of personal, dyadic, and family resources

Abstract: Findings contribute to caregiver intervention efforts by highlighting important resources associated with subjective stressors across time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
(26 reference statements)
0
15
0
1
Order By: Relevance
“…Studies of Zairt and Bangerter have also shown that most of the families have conflicts related to caregiving. 16,50 And conflicts between many adult children are mostly focused on the task of caring for the elderly and economic issues, 17,19 which seriously affect the FA and relatives' support in the patient's family. Interventions intended to promote FA and kinship support can be carried out by helping adult children to reasonably resolve role conflicts and promoting effective communication to reasonably distribute tasks between adult children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of Zairt and Bangerter have also shown that most of the families have conflicts related to caregiving. 16,50 And conflicts between many adult children are mostly focused on the task of caring for the elderly and economic issues, 17,19 which seriously affect the FA and relatives' support in the patient's family. Interventions intended to promote FA and kinship support can be carried out by helping adult children to reasonably resolve role conflicts and promoting effective communication to reasonably distribute tasks between adult children.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to control the confounding effect produced by family stressors, they were measured too. According to the characteristic of stressors in family of patients with dementia, 16,39,40 the stressors were measured by The Revised Memory and Behavior Problems Checklist (RMBPC), Activity of Daily Living (ADL), and Family Inventory of Life Events and Changes (FILE).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…48,49 Dyadic relational quality is of paramount importance in other caregiving settings, including dementia caregiving, where higher relationship quality has been linked to lower subjective care stressors, such as role captivity and role overload. 50 Thus, educational and support services for caregivers should consider promoting positive relational functioning within the caregiver/care-recipient dyad.…”
Section: Discussionmentioning
confidence: 99%